Analysis of association between eating behaviours and childhood obesity among pre-school children: A cross-sectional study - Wu, Yi-Xin; Fan, Hai-Ling; Dai, Jin; Wu, Hui-Lan; Yang, Jing-Yun; Wang, Yun; Tung, Tao-Hsin; Wang, Li-Zhen; Zhang, Mei-Xian (Frontiers in Pediatrics, 2023)
Background: Childhood obesity is a worldwide critical health concern. We aimed to clarify whether eating behaviours increased the risk of childhood obesity. Methods: We recruited 2049 pre-school children aged 3–6 years between 1 December 2021 and 31 January 2022 in Taizhou, China. Children’s weight status was classified according to the International Obesity Task Force criteria, and their eating behaviours were evaluated using the Children’s Eating Behaviour Questionnaire. Correlation analyses, linear regressions, and one-way ANCOVA. were performed to analyse the association between children’s eating behaviours and weight status. Results: In ‘Food Avoidant’ subscales, the scores of satiety responsiveness (P<0.001) and slowness in eating (P=0.001) were negatively associated with body mass index z score among pre-school children of both sexes. In ‘Food Approach’ subscales, the score of enjoyment of food was positively associated with body mass index z score in both boys (P=0.007) and girls (P=0.035), but the association of scores of food responsiveness with body mass index z score was found only in girls (P=0.001). Conclusion: Our results supported that pre-school children with low scores in ‘Food Avoidant’ subscales and high scores in ‘Food Approach’ scales were more likely to become obese.